2016
DOI: 10.3310/hsdr04280
|View full text |Cite
|
Sign up to set email alerts
|

Models of care for the delivery of secondary fracture prevention after hip fracture: a health service cost, clinical outcomes and cost-effectiveness study within a region of England

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms VOLUME 4 ISSUE 28 SEPTEMBER 2016 ISSN 2050 DOI 10.3310/hsdr04280 HEALTH SERVICES AND DELIVERY RESEARCHModels of care for the delivery of secondary fracture prevention after hip fracture: a health service cost, clinical outcomes and cost-effectiveness study within a region of England … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 120 publications
(258 reference statements)
1
61
1
9
Order By: Relevance
“…For patients who experience OPrelated fractures, a cost burden is also placed on primary care. A study of UK databases reported that primary care costs increased significantly in the first 2 years after hip fracture [8]. Coordinator-based fracture liaison services for secondary prevention also usually require the GP's involvement as part of a multi-disciplinary team for treating patients and monitoring their progress [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For patients who experience OPrelated fractures, a cost burden is also placed on primary care. A study of UK databases reported that primary care costs increased significantly in the first 2 years after hip fracture [8]. Coordinator-based fracture liaison services for secondary prevention also usually require the GP's involvement as part of a multi-disciplinary team for treating patients and monitoring their progress [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Orthogeriatric models of care have demonstrated being the future for the elderly fractured patient, with a special interest in the organization of an additional estructure of secondary prevention that it is giving extraordinary results, the Fracture Liason Services. 128,[142][143][144][145]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fracture units (FLS) have also been implemented, where the cause is studied, patients are monitored, and secondary prevention of osteoporosis is undertaken, also achieving better adherence to the treatment, improvement in BMD, and a reduction in new fractures as well as mortality. 137,144,145 Both methods, Orthogeriatric Units and FLS, must be considered as a work mode when the objective is the secondary prevention of fractures in geriatric patients.…”
Section: Methods For the Treatment Of Fractures And The Secondary Prevmentioning
confidence: 99%
“…The workforce impact and issues surrounding the running of an FLS were assessed in a qualitative analysis of interviews with 43 health professionals in the United Kingdom, all of whom had been involved in FLS [41]. Significant themes included communication, resourcing and adherence.…”
Section: Evidence For Effectiveness Of Flsmentioning
confidence: 99%